Legality of Marine Cargo Insurance Claim With Different Sailing Date on Policy (Analysis of Decisions Number 589/PDT.G/2012/PN.JKT.SEL) - Krisna Angela; Dian Purnama Anugerah (Yuridika, 2023)
Sailing dates in marine cargo insurance often change for various reasons. It is unavoidable that from the time the ship sail on a date that is not under the policy, uncertain events occur, which cause losses. On the other hand, insurance recognizes the principle of utmost good faith, which obliges the insured to disclose material facts about the insured object correctly, completely, and honestly as regulated in Article 251 WvK. It creates a blurring of norms because that rule make the parties debating whether the ship's sailing date is a material fact or not. This research uses normative legal research methods with a statute approach, conceptual approach, and case approach. This research purposed to analyze changes in sailing date as material facts and the consequences of not disclosing these changes by the insured to the insurer and the insurer to the reinsurer by analyzing Decision Number 589/Pdt.G/2012/PN.Jkt.Sel. The results of this study indicate that the change in sailing date is a material fact that must be disclosed by the insured to the insurer. When the insured does not disclose material facts, it can make a contract voidable and the insurer can be free from the obligation to pay claims. In addition, the Judge's decision in Decision Number 589/Pdt.G/2012/PN.Jkt.Sel was wrong because the Judge did not analyze the meaning and concept of material facts in marine cargo insurance as regulated in Article 251 WvK and did not consider the provisions in the policy referring to the Marine Insurance Act 1906.